1999
DOI: 10.1128/jb.181.1.133-140.1999
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Characterization of the Protein Template Controlling Biosynthesis of the Lipopeptide Lichenysin

Abstract: Lichenysins are surface-active lipopeptides with antibiotic properties produced nonribosomally by several strains of Bacillus licheniformis. Here, we report the cloning and sequencing of an entire 26.6-kb lichenysin biosynthesis operon from B. licheniformis ATCC 10716. Three large open reading frames coding for peptide synthetases, designated licA, licB(three modules each), and licC (one module), could be detected, followed by a gene, licTE, coding for a thioesterase-like protein. The domain structure of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 54 publications
3
63
0
1
Order By: Relevance
“…This arrangement has also been reported for several NRPS [10][11][12][13][14]. It is suggested that the first amino acid could be initially acylated with a fatty acid in this domain [12]. When D-amino acid residues show up in the peptide products, the available L-isomers will be typically selected by Adomains and then epimerized by downstream E-domain.…”
Section: C-domains Of Arthrofactin Synthetasesupporting
confidence: 67%
See 1 more Smart Citation
“…This arrangement has also been reported for several NRPS [10][11][12][13][14]. It is suggested that the first amino acid could be initially acylated with a fatty acid in this domain [12]. When D-amino acid residues show up in the peptide products, the available L-isomers will be typically selected by Adomains and then epimerized by downstream E-domain.…”
Section: C-domains Of Arthrofactin Synthetasesupporting
confidence: 67%
“…One additional C-domain (namely ArfA_C1) was identified in the first module of ArfA. This arrangement has also been reported for several NRPS [10][11][12][13][14]. It is suggested that the first amino acid could be initially acylated with a fatty acid in this domain [12].…”
Section: C-domains Of Arthrofactin Synthetasesupporting
confidence: 64%
“…[32,33] A similar mechanism is observed in lichenysin biosynthesis where the third module responsible to incorporate l-Ile is also reported to be replaced by l-Val and l-Leu with about one quarter incorporation efficiency. [34] Analysis of VLM BGC by antiSMASH, predicts that A domain in module 4 could incorporate valine or isoleucine according to the NRPSPredictor (most similar activesite signature in the specificity conferring code proposed by Stachelhaus et al). [35] Consequently we propose a distinct Val substitution by Ile for these series of homologues compounds.…”
mentioning
confidence: 99%
“…According to the organization and the structure of the formed products, it can be concluded that these C-domains are probably involved in peptide-chain termination and cyclization [41]. In other bacterial PS systems, such as lichenysin [42], surfactin [43] or fengycin [44], the presence of an additional C domain located in the N-terminal end has been correlated with the fact that the first amino acid of the product peptide is acylated Table 1 Signature sequences of putative adenylation domains of the Trichoderma fragments obtained by degenerate PCR and from Salps1 [19] Module…”
Section: T Harzianum Cect 2413 Ps Genementioning
confidence: 99%